2015
DOI: 10.1016/j.jinf.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of diarrhea among children under the age five in China: Results from a five-year surveillance

Abstract: Summary Objectives Diarrhea is a leading cause of morbidity and mortality for children, although sparse data is available on the etiology of diarrhea in China. This study was conducted to determine main causes that underlie childhood diarrhea and related diseases. Method Surveillance data for diarrhea was collected from 213 participating hospitals between 2009 and 2013. These stool specimens, from children aged 0e59 months, were then analyzed for a panel of etiological agents consisting of 5 viruses, 8 bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
90
6
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 17 publications
(21 reference statements)
13
90
6
3
Order By: Relevance
“…In 7 samples the P genotype was identified but the G genotype was still not distinguished, and in 9 RVA specimens the G genotype was defined but P genotype remained negative; 333 (95.4%) samples were identified to have both G and P genotypes. G9P(8) strains had the highest score (58.2%), followed by: G3P(8) (14.9%); G1P(8) (6.9%); G3G1P(8) (5.2%); G3P(4), G8P(9), and G9P(4) (1.1%); G1P(4), G2P(8), G4P (8), and G1G2P(4) (0.9%); G2P(6), G3P(9), G4P(6), G9P(6), and G1G9P(8) (0.6%); and G4P(4) and G2P(4)P(8) (0.3%) ( Table 2). These data suggested that G9P(8) strains are prevalent among children infected with RVA in Kunming, China.…”
Section: Common Genotypes Among Diarrhea Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 7 samples the P genotype was identified but the G genotype was still not distinguished, and in 9 RVA specimens the G genotype was defined but P genotype remained negative; 333 (95.4%) samples were identified to have both G and P genotypes. G9P(8) strains had the highest score (58.2%), followed by: G3P(8) (14.9%); G1P(8) (6.9%); G3G1P(8) (5.2%); G3P(4), G8P(9), and G9P(4) (1.1%); G1P(4), G2P(8), G4P (8), and G1G2P(4) (0.9%); G2P(6), G3P(9), G4P(6), G9P(6), and G1G9P(8) (0.6%); and G4P(4) and G2P(4)P(8) (0.3%) ( Table 2). These data suggested that G9P(8) strains are prevalent among children infected with RVA in Kunming, China.…”
Section: Common Genotypes Among Diarrhea Casesmentioning
confidence: 99%
“…Molecular epidemiological studies have distinguished 27 G genotypes and 35 P genotypes. Of major worldwide epidemiological importance are the genotypes G1P(8), G2P(4), G3P(8), G4P (8), and G9P (8) and, to a lesser extent, G12P(8) [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately, 80% of the total diarrhoea incidence relates to children younger than two years of age (Walker et al, 2013). After this age, the rate of illness falls as the first infections induce a certain level of immunity, which protects against following incidences (Yu et al, 2015). Gender is also important, because of differences in immune system functioning between girls and boys, and because girls have been shown to have lower morbidity and mortality rates than boys (Muenchhoff & Goulder, 2014).…”
Section: Control Factorsmentioning
confidence: 99%
“…For this purpose, the articles, which children under the age five [17] . Age group of 6-23 month-old children and that of people over 45 years old were found with the highest positive percentage, 13.7% and 12.4% respectively.…”
Section: Introductionmentioning
confidence: 99%